Duality of practice in clinical research nursing. (March 2022) - Hill, Gordon; Ellis, Mairghread; Irvine, Lindesay
Background: International evidence suggests that Clinical Research Nurses (CRN) can have a dual role incorporating both clinical care and research responsibilities. This duality of role often assists in meeting the clinical care and research needs of the participants and can contribute to the credibility of the CRN role. Conversely, it can also lead to feelings of confusion and role conflict as CRN's time is divided. Aim: To identify and explore experiences of clinical and research roles among CRNs. This emerged as a theme in a wider research project exploring CRNs' experiences of working with clinical nurses. Methods: Following an Interpretative Phenomenological Analysis approach, 10 CRNs participated in face-to-face semi-structured interviews. Transcribed data were analysed and a number of themes emerged. Duality of role was one of these. Findings: Findings indicated that if CRNs fulfil a dual role, this can assist in care provision, research delivery and in building positive relationships with clinical nurses. However, there were also instances when a dual role led to clinical nurses questioning the value of research and to issues with competing demands of clinical care and research. These experiences had an important impact on some of the CRNs and led to reflection on the value of their role. Conclusions: This study identifies new understandings of a dual role of the CRN. The findings will inform the preparation and practice of this group of nurses, whilst also leading to a deeper understanding of the CRN's role in care and research delivery. It will also contribute to a wider appreciation of organisational factors and social interactions that impact on health care research.